Faktor-Faktor Yang Mempengaruhi Besarnya Remitan Keluarga TKI Di Kabupaten Pasuruan - Lazuardy Aji Cahyadi; Wibisiono Sunlip; Endah Kurnia Lestari (Jurnal Ekonomi Pembangunan, 2021)
Migration is the movement of people from their place of origin to their destination. The primary purpose of migration is to improve the standard of living of their families so that, in general, they are looking for work that can provide higher income and social status in the destination area. Remittance is transfers of money, good, development ideas from the destination of migration to the place of origin and are an essential instrument in the socio-economic life of a society. This study aims to determine the factors that influence the size of remittances to the families of TKI in Pasuruan Regency. This research uses a quantitative research type with primary data, and the analytical tool uses multiple linear regression with cross-section data. The results of the analysis show that the income of TKI and the number of family dependents has a positive and significant effect, while the length of time for TKI to work has a positive but insignificant impact on the amount of remittance sent to TKI’s family in Pasuruan Regency.